In Vivo Antiplasmodial Activity and Toxicological Analyses of the Ethanolic Leaf and Twig Extract of Faurea speciosa Welw. (Proteaceae) - Felix Ayisi; Caleb Nketia Mensah; Lawrence Sheringham Borquaye (Journal of Parasitology Research)
In Africa, medicinal plants are commonly used to treat malaria and other diseased conditions. The ethanolic leaf and twig extract of Faurea speciosa has been shown to possess promising antiplasmodial properties. This present study was aimed at investigating its antiplasmodial effect in vivo. Qualitative phytochemical screening was carried out on the plant samples using standard methods. The antiplasmodial effect against early infection, curative effect against established infection, and prophylactic effect against residual infection were studied in vivo in Plasmodium berghei-infected mice while the carrageenan-induced edema model in chicks was used for anti-inflammatory tests. The phosphomolybdenum and DPPH radical scavenging assays were used in the evaluation of antioxidant potential. Acute toxicity of the extract was evaluated using the Organization for Economic Cooperation and Development (OECD) guidelines. Phytochemical screening of plant samples revealed the presence of flavonoids, coumarins, tannins, saponins, and glycosides. Faurea speciosa leaf and twig extract exhibited significant antiplasmodial activities in the mouse model with parasite suppression rates of 66.63%, 71.70%, and 56.93% in the suppressive, curative, and prophylactic tests, respectively. A 55.50% reduction of edema in the anti-inflammatory test indicated moderate success in reducing inflammation. The total antioxidant capacity of the extract was determined to be 65.4 mg AAE/g of extract, while in the DPPH radical scavenging assay, the IC50 value was found to be 499.4 μg/mL. With the exception of an inconsistent rise in urea level, there was no significant difference in the other biochemistry parameters in the acute toxicity studied. The median lethal dose (LD50) of the extract was over 2000 mg/kg. The results of this study show that Faurea speciosa leaf and twig extract has promising antimalarial capabilities and is fairly safe at low concentrations.